PENINGKATAN PEMAHAMAN SEKAA TERUNA-TERUNI DESA TARO, TENTANG INVENTARISASI DAN KONSERVASI BENDA CAGAR BUDAYA - N.K.P, Ast iti Laksmi; Wiguna, I G.N.Tara; Wardi, I N.; Bawono, R. A.; Jaya, I B. Sapta; Zuraidah, Zuraidah; Titasari, C. Pelupi (Buletin Udayana Mengabdi; Vol 10 No 1 (2011): Volume 10 No.1 – April 2011, 2012)
The provisioning of comprehension about cultural heritage and conservation to the young generations can work out with education and training. Application of methods are presentation with discussion and training of conservation. The advance of comprehension signification about cultural heritage is indicated by the advance percentage from 23 respondents (76,6%) became 30 respondents (100%), about rescuing of cultural heritage from 30 respondents (100%) became 30 respondents (100%), about inventory from 27 respondents (90%) became 30 respondents (100%). And for conservation become 30 respondents (100%) from 27 respondents (90%). The result shows that technique of education and training is efective for advanced respondents’ comprehension about cultural hetitage and concervation.